Development of delayed ripening papaya (Carica papaya L.) CV. 'eksotika' using RNA interference and antisense technologies - Sekeli, Rogayah (2013)
Papaya (Carica papaya L.) is a popular fruit in the world. In Malaysia,among the popularly grown cultivar is Eksotika, introduced by MARDI in 1987. Similar to other tropical fruits, an Eksotika fruit has a very short shelflife, which limits its export potential to distant destinations. Hence, there is a need to extend its shelf-life in order to reduce post-harvest losses and to increase its export potential to distant markets. This project is aimed at extending the shelf-life of the highly perishable Eksotika papaya fruit. Fruit ripening is closely related to the production of ethylene gas within the fruit. One way to extend the shelf life of papaya fruit is by manipulating the activities of the enzymes involved in ethylene biosynthesis. It was hypothesized that reduction in the production of ethylene would result in lengthening the shelf-life of the fruit. In this study, RNA interference (RNAi) and antisense RNA technologies were applied to manipulate and transform both genes encoding 1-aminocyclopropane-1-carboxylic acid (ACC) oxidase 1 (designated as ACO1) and 2 (designated as ACO2) into Eksotika papaya embryogenic cultures. It was reported ACO2 is closely associated with fruit ripening characteristic compared to ACO1. Thus for the antisense study, only ACO2 gene manipulation was pursued. A total of 15,000 embryogenic calli of Eksotika papaya were transformed with the three different RNAi constructs (pRNAiACO1, pRNAiACO2 and pRNAiCACO) constructs and 6,000 with the antisense ACO2 construct. A total of 148 positive putative transformants were recovered using the RNAi constructs, and 46 using the antisense ACO2 construct. Gene expression analysis using real-time RT-PCR on the antisense putative transgenic R0 plants showed between two to five folds down- regulation of the ACO2 in 42 putative transgenic R0 plants with the highest reduction shown in R0 3-1 and R0 27-3. For RNAi, 9 independent R0 plants were tested and all showed between two to three folds down- regulation of the ACO genes. An improved and efficient rooting method was established for the regenerated putative transgenic Malaysian Eksotika papaya shoots. The rooting percentage was increased to 92.5% using the half strength Murashige & Skoog (MS) ingredients mixed with vermiculite compared to 22% using the original method comprised of the De Fossard medium. The survival rate of the rooted shoots after transfer into the ground was 92%. Morphohistological analyses revealed that the tap roots of the shoots were more compact, which might have contributed to their high survival rates. A total of 31 independently selected RNAi plants and 24 antisense plants were transferred into soil and grown under nethouse condition for assessment of delayed ripening characteristic of the papaya fruits. Twenty RNAi and 13 antisense transgenic R0 plants showed single copy number. Statistical analysis showed no significant difference (p<0.05) in plant growth performance between transgenic and non-transformed seedling-derived plants. Shelf-life analysis of the transgenic fruits showed that fruits from 11 transgenic antisense R0 plants exhibited delayed fruit ripening with the most potential, transgenic R0 27-3, remaining green for 14 days compared to the control (4 days). For RNAi transgenic plants, fruits from 13 R0 plants showed delayed ripening, with the most potential R0 plants pRNAiACO2 L2-9 and pRNAiACO1 L2 exhibited about 20 and 14 days post-harvesting to reach the full maturity index (Index 6), respectively. The total soluble solid (TSS) of the transgenic fruits was comparable to the control fruits with similar 11-14°Brix. The transgenic fruits remained firm for additional 4 to 8 days at room temperature (25 ± 2ºC) after achieving Index 6 while the nontransformed seed-derived fruits lost their firmness after 2 days. Histological studies on the transgenic and control fruits at Index 2 and Index 6 showed significant differences in their cells morphology. Overall, the findings in this study demonstrated that reduction of ethylene was successful in the Eksotika papaya by manipulating the ACO gene(s) using the antisense RNA and RNAi techniques. This reflects that future production of longer shelflife Eksotika papaya fruits is possible with either antisense RNA or RNAi.